1994
DOI: 10.1128/jb.176.24.7646-7652.1994
|View full text |Cite
|
Sign up to set email alerts
|

Wild-type gas vesicle formation requires at least ten genes in the gvp gene cluster of Halobacterium halobium plasmid pNRC100

Abstract: To study the functions of the 13 gyp genes, gvpMLKJIHGFEDACN, on plasmid pNRC100 of Halobacterium halobium in gas vesicle formation, we carried out linker scanning mutagenesis of the gene cluster. We constructed a 24.5-kb Escherichia coli-H. halobium shuttle plasmid, pFL2, containing the gyp gene cluster and introduced a kanamycin resistance (K) cassette into each gene (except for gvpA). Transformation of H. halobium SD109, which had the entire gyp gene cluster deleted, with pFL2 and mutated pFL2 derivatives s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
91
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 23 publications
(25 reference statements)
5
91
3
Order By: Relevance
“…These gas vesicle proteins (Gvps) are encoded by a cluster of gvp genes ( Figure 1). Early gene disruption experiments indicated that 13 gvp genes are essential for wild-type gas vesicle formation in halophilic archaea [3], whereas the findings of a more recent study suggest that eight genes, gvpFGJKLM-gvpAO, suffice [4]. GvpA represents the major envelope component.…”
Section: Introductionmentioning
confidence: 97%
“…These gas vesicle proteins (Gvps) are encoded by a cluster of gvp genes ( Figure 1). Early gene disruption experiments indicated that 13 gvp genes are essential for wild-type gas vesicle formation in halophilic archaea [3], whereas the findings of a more recent study suggest that eight genes, gvpFGJKLM-gvpAO, suffice [4]. GvpA represents the major envelope component.…”
Section: Introductionmentioning
confidence: 97%
“…Also, the CbbQ gene product, a MoxR-related protein, was shown to alter Rubisco 4 conformation and stimulate its activity upon overexpression of recombinant forms of the proteins together in an Escherichia coli system (13,14). Yet another MoxR family member, GvpN, has been shown to be important in gas vesicle biogenesis in certain organisms (15)(16)(17)(18). The exact role and mechanism of function of MoxR proteins in all of these processes are not clear.…”
mentioning
confidence: 99%
“…Fourteen gvp genes are involved in the formation of these gas-filled proteinaceous particles, arranged as two oppositely oriented clusters, gvpACNO and gvpDEFGHIJKLM (Englert et al, 1992a;DasSarma et al, 1994). Hbt.…”
Section: Introductionmentioning
confidence: 99%